Meningkatkan Produktivitas Siswa dalam Pembelajaran Bahasa Indonesia di Era Digital - Iswatiningsih, Daroe (Kajian Bahasa dan Sastra (KABASTRA), 2023)
The use of technology in the world of education has a very big role, especially after the Covid19 pandemic. In the educational environment, teachers, students, and education staff are required to master technology in order to streamline and streamline learning. This has continued into the post-covid 19 pandemic. Learning today is offline sometimes blended learning by utilizing various applications of technology so that students learn to be happy, interactive, communicative, and critical thinking. Learning that develops students' affective, cognitive and psychomotor competencies is expected to build life skills and meaning for students. The Merdeka Belajar government program provides a very wide space for teachers and students to be creative in exploring, growing and developing students' life skills that are utilized in everyday life. Life skills in learning Indonesian oriented towards the ability to communicate orally or in writing well. For this reason, the substance of the material, strategies and methods as well as the output of important competencies are well planned by the teacher. Learning productivity Indonesian boils down to four aspects, namely listening, speaking, reading and writing which are supported by the use of technology, as in today's digital era.